Solid Medical Waste Management of Hazardous and Toxic at UNS Hospital Surakarta - Hashfi Hawali Abdul Matin; Purwono Purwono; Achmad Chalid Afif Alfajrin; Awaluddin Hidayat Ramli Inaku (Universitas Diponegoro, 2022)
In the era of the COVID-19 Pandemic, medical waste is increasing in various hospitals, including UNS Hospital. The variables studied in the hazardous and toxic solid medical waste flow treatment. Primary data was obtained from an analysis of waste amount in 2021 and interviews with incinerator managers. Secondary data in the form of waste types, impacts, and incinerator residue were obtained from the literature study. This research aims to identify solid medical waste management with hazardous and toxic materials compared with Regulation of Environment and Forestry Minister of Republic Indonesia 56/2015. After analysis, it was found that there is dangerous and harmful solid medical waste flow management, distinguished by type. Particular colored medical waste is managed by reducing, sorting, storing, transporting, and destroying. Destruction is conducted with an incinerator. Arah Environmental Indonesia Company operates infectious medical waste. The potential impact of that waste can attack health, damage the environment quality, increase the degradation that has occurred, and pose a threat to microplastic. Completing waste management is done by tightening hospital regulations to produce output according to quality standards, limiting hazardous and toxic waste use, and selecting the waste.